LINGUISTIC MEANS OF EXPRESSING HUMOUR - Temirkhanova, D.A. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Playing with words is a part of everyday communication that can be produced by everyone. Such wordplays have different types and functions which could be used almost everywhere. They play the most important role in humour sphere. Humour is widely known as a part of human-beings life. Although, not everyone knows how to make jokes skillfully and what expressive means and stylistic devices were used. As a result, people don’t use different existing methods of expressing humour.
Keywords: Expressive means and stylistic devices; humour; methods of expressing humour; pun; simile; exaggeration; metaphor